Effect of yoga and probiotic intervention on hormonal parameters in pre-menopausal women with polycystic ovary syndrome - Kumaravelu, Ranjane; V. R., Bharathi Dhevi; Thulasi, Arun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic ovary syndrome (PCOS) affects reproductive and metabolic health in pre-menopausal women, necessitating innovative therapeutic approaches. This study investigated the combined effects of yoga and probiotic supplementation on hormonal parameters and fertility outcomes compared to yoga alone and control groups. Methods: Forty pre-menopausal women (35-55 years) diagnosed with PCOS were allocated to three groups: control (n=10), yoga intervention (n=15), and yoga with probiotic supplementation (n=15). The yoga intervention consisted of standardized 30-minute sessions three times weekly for three months. The combined group practised yoga and consumed 5 gm dry-roasted powdered flaxseed in 100 ml of buttermilk twice daily. Primary outcomes included reproductive hormones (E2, FSH, LH, Prolactin), thyroid function (FT3, FT4, TSH), haemoglobin levels, and pregnancy outcomes. Results: The control group showed no hormonal changes. The yoga-only group demonstrated modest improvements in thyroid function (FT3-12.1%, TSH-8.2%) with minimal reproductive hormone effects. The yoga with probiotics group showed substantial improvements: E2 increased 15.9%, while FSH (-15.0%), LH (-18.7%), and prolactin (-17.5%) decreased significantly. Significantly, 33.3% of participants in the yoga with probiotics group achieved pregnancy during the intervention period, while no pregnancies occurred in other groups. Conclusions: Combining yoga with probiotic supplementation demonstrates superior efficacy in improving hormonal profiles and fertility outcomes in pre-menopausal women with PCOS compared to yoga alone, offering a promising integrative therapeutic approach.